2021
DOI: 10.7861/clinmed.2021-0503
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pregnancy

Abstract: Pregnant women with COVID-19 are less likely to be symptomatic than non-pregnant counterparts. Risk factors for severe disease include being overweight or obese, greater than 35 years old, and having pre-existing comorbidities. Those who develop severe disease have increased rates of admission to an intensive care unit, requiring invasive ventilation and pre-term birth.Pregnant and breastfeeding women with COVID-19 should be investigated as of outside pregnancy and should receive proven therapies (such as cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 9 publications
4
29
0
7
Order By: Relevance
“…1 Compared with nonpregnant women of childbearing age with SARS-CoV-2 infection, pregnant women are more likely to be needed for respiratory support and admitted to an ICU. 2 Pregnant women with SARS-CoV-2 infection are at high risk for adverse perinatal outcomes such as early pregnancy loss, fetal growth retardation, and preterm delivery. 3,4 Impaired placental function, hypoperfusion, and inflammation might lead to fetal decompensation that increased risk of perinatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Compared with nonpregnant women of childbearing age with SARS-CoV-2 infection, pregnant women are more likely to be needed for respiratory support and admitted to an ICU. 2 Pregnant women with SARS-CoV-2 infection are at high risk for adverse perinatal outcomes such as early pregnancy loss, fetal growth retardation, and preterm delivery. 3,4 Impaired placental function, hypoperfusion, and inflammation might lead to fetal decompensation that increased risk of perinatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome Coronavirus 2 (SARS‐CoV‐2) infection is a major public health problem, with hospitalizations, admissions to the intensive care unit (ICU), and even deaths 1 . Compared with non‐pregnant women of childbearing age with SARS‐CoV‐2 infection, pregnant women are more likely to be needed for respiratory support and admitted to an ICU 2 . Pregnant women with SARS‐CoV‐2 infection are at high risk for adverse perinatal outcomes such as early pregnancy loss, fetal growth retardation, and preterm delivery 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that pregnant women also comprise a vulnerable group, with higher rates of intensive care unit (ICU) admission and mechanical ventilation when compared to non-pregnant adults of a similar age group [ 5 ]. As reported in non-pregnant adults, pre-existing comorbidities like hypertension, diabetes, high maternal age, and obesity have been identified as risk factors for severe COVID-19 disease in pregnancy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, pregnant women are a vulnerable group, with a greater risk of COVID-19 morbidity and mortality, increasing the risk of adverse pregnancy outcomes [ 1 ]. In this context, statistics from the UK reported a total of 9% of pregnant women and 6-week postpartum COVID-19 admissions to intensive care units (ICU) [ 2 ], while a review highlighted that most infections occurred during the third trimester, 11% of pregnant women with COVID-19 required admission to ICU, and 8% required mechanical ventilation [ 3 ]. It has also been reported that prevalence among women is variable, rising from 0.5% to 5% in the span of 2 weeks [ 4 ].…”
Section: Introductionmentioning
confidence: 99%